2022
DOI: 10.2106/jbjs.rvw.21.00147
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Disorders of the Pediatric Thumb

Abstract: » Surgical timing for pediatric trigger thumb treatment is controversial for numerous reasons including the potential for spontaneous resolution, the possibility of bilateral involvement, and anesthesia concerns regarding the developing brain. Hence, a reasonable approach is to delay the surgical procedure until the patient is ≥3 years of age.» Preaxial polydactyly is usually unilateral and sporadic, with the most common reconstruction method consisting of excision of the diminutive thumb with preservation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 91 publications
(138 reference statements)
0
7
0
Order By: Relevance
“…35,36 ►Table 4 details the structural and functional changes that occur during pollicization. 26 Overall, both thumb hypoplasia reconstruction and index pollicization do well. One review of ADM opponensplasty showed mean postoperative key pinch strength of 40% when compared with normal age-matched controls.…”
Section: Hypoplastic Thumbmentioning
confidence: 97%
See 1 more Smart Citation
“…35,36 ►Table 4 details the structural and functional changes that occur during pollicization. 26 Overall, both thumb hypoplasia reconstruction and index pollicization do well. One review of ADM opponensplasty showed mean postoperative key pinch strength of 40% when compared with normal age-matched controls.…”
Section: Hypoplastic Thumbmentioning
confidence: 97%
“…25 It is important to screen these patients for associated syndromes, the most common being Fanconi anemia, thrombocytopenia absent radius syndrome, Holt–Oram syndrome, and vertebral anomalies, anal atresia, cardiac anomalies, tracheoesophageal fistula, renal defects, and limb anomalies association ( Table 2 ). 26 Initial workup should include spinal radiographs, echocardiogram, complete blood-cell count, abdominal ultrasound, and possibly chromosomal breakage test (i.e., diepoxybutane testing) to rule out Fanconi anemia. 25 27 Surgical reconstruction of the hypoplastic thumb should only be performed after obtaining appropriate medical clearance.…”
Section: Hypoplastic Thumbmentioning
confidence: 99%
“…It follows an autosomal dominant inheritance model with reduced penetrance[ 4 ]. Thumb polydactyly has been further subdivided into six subtypes by Wassel according to the level of (metacarpal, proximal, or distal phalange) and the extent of duplication (partial and complete)[ 5 , 6 ]. Next generation sequencing (NGS) analysis in a patient with Wassel III polydactyly identified three gene mutations as follows: (1) Substitution c.1639 G>T in RPGRIP1 gene; (2) Insertion of adenine in TMEM216 gene; and (3) A>G nucleotide substitution (c.490) in FBN1 gene.…”
Section: Polydactylymentioning
confidence: 99%
“…16 Hypoplastic variations are more often seen with congenital malformations and in the setting of Holt-Oram syndrome, Blackfan-Diamond syndrome, and Fanconi anemia. 7,17,18 With profound variability in clinical presentation, many authors have sought to delineate classification schemes, but without substantial success in attaining uniform use. Published classification systems focus on the clinical features of the triphalangeal thumb, such as the shape of the accessory phalanx, [20][21][22] opposition, [23][24][25] syndactyly and polydactyly, 7 and type of polydactyly present.…”
Section: Introductionmentioning
confidence: 99%